Astragalus membranaceus–Derived Anti-Programmed Death-1 Monoclonal Antibodies with Immunomodulatory Therapeutic Effects against Tumors. (4th March 2020) - Chang, Fu-Ling; Tsai, Keng-Chang; Lin, Tsai-Yu; Yang, Tz-Wen; Lo, Yan-Ni; Chen, Wang-Chuan; Chang, Jui-Hsien; Lu, Mei-Kuang; Chiou, Chun-Tang; Chen, Po-Hung; Yen, Yun; Pan, Shiow-Lin; et al.
Abstract : Astragalus membranaceus polysaccharide (APS) components are main ingredients of TCM and have proven efficacy to activate T cells and B cells, enhancing immunity in humans. In this study, elevated cytokine and anti-PD-1 antibody titers were found in mice after immunization with APS. Therefore, phage-display technology was utilized to isolate specific anti-programmed death-1 (PD-1) antibodies from mice stimulated by APS and to confirm whether the isolated anti-PD-1 antibody could inhibit the interaction of PD-1 with the programmed death-ligand 1 (PD-L1), resulting in tumor growth inhibition. The isolated single-chain fragment variable (scFv) S12 exhibited the highest binding affinity of 20 nM to PD-1, completed the interaction between PD-1 and PD-L1, and blocked the effect of PD-L1-induced T cell exhaustion in peripheral blood mononuclear cells in vitro. In the animal model, the tumor growth inhibition effect after scFv S12 treatment was approximately 48%. However, meaningful synergistic effects were not observed when scFv S12 was used as a cotreatment with ixabepilone. Moreover, this treatment caused a reduction in the number of tumor-associated macrophages in the tumor tissue. These experimental results indirectly indicate the ability of APS to induce specific antibodies associated with the immune checkpoint system and the potential benefits for improving immunity in humans.